2022
DOI: 10.1002/lio2.768
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for hearing outcomes in patients that undergo adjuvant hyperbaric oxygen therapy for sudden sensorineural hearing loss

Abstract: Introduction:The aim of this study is to explore the potential factors in hearing outcomes and verify the role of oxidant-antioxidant equilibrium on the prognosis of sudden sensorineural hearing loss (SSNHL) treated with hyperbaric oxygen therapy (HBOT).Methods: Ninety-two patients who were diagnosed with SSNHL between January 2018 and December 2019 in our hearing clinic center were included in this study. All patients were treated with intravenous dexamethasone, and 72 cases were treated with additional HBOT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…We showed that combining HBOT and medical therapy improved recovery (80.0% versus 57.1%) and hearing gain (25.1 ± 11.9 dB versus 13.3 ± 6.8 dB), compared to medical therapy alone. Consistent with our findings, several systematic reviews have shown that adding HBOT to steroid therapies can benefit patients with severe to profound ISSHL [ 4 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We showed that combining HBOT and medical therapy improved recovery (80.0% versus 57.1%) and hearing gain (25.1 ± 11.9 dB versus 13.3 ± 6.8 dB), compared to medical therapy alone. Consistent with our findings, several systematic reviews have shown that adding HBOT to steroid therapies can benefit patients with severe to profound ISSHL [ 4 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…It a ects approximately 5−27 per 100,000 people annually, but its incidence has been increasing over the past decades [1][2][3]. Although its pathogenesis is incompletely understood, the most common triggers involve viral infections, vascular disorders, and autoimmune factors [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the pathogenic causes of SSNHL are still debated, and several possible etiologies have been proposed, including viral infection, vascular disorders, trauma and autoimmune diseases ( Shen et al, 2021 ; Wu et al, 2022a ; Feng et al, 2022 ). As a medical emergence, detailed examination to determine possible causes and early treatment onset is extremely important to improve hearing prognosis in SSNHL patients ( Jiang et al, 2021 ; Huo et al, 2022 ). Although numerous studies were performed to determine the diagnostic and prognostic biomarkers in SSNHL, no reliable indicator was available in practice ( Huo et al, 2022 ; Park et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a medical emergence, detailed examination to determine possible causes and early treatment onset is extremely important to improve hearing prognosis in SSNHL patients ( Jiang et al, 2021 ; Huo et al, 2022 ). Although numerous studies were performed to determine the diagnostic and prognostic biomarkers in SSNHL, no reliable indicator was available in practice ( Huo et al, 2022 ; Park et al, 2022 ). Recently, an increasing number of evidence showed that metabolic diseases were independent risk factors for the occurrence of SSNHL, and pathoglycemia and dyslipidemia significantly affected hearing recovery ( Doo et al, 2020 ; Chen et al, 2022a ; Simões et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%